NF‐κB mediated miR‐26a regulation in cardiac fibrosis1. Issue 7 (21st March 2013) - Wei, Chuanyu; Kim, Il‐Kwon; Kumar, Sandeep; Jayasinghe, Samantha; Hong, Nayeon; Castoldi, Giovanna; Catalucci, Daniele; Jones, W. Keith; Gupta, Sudhiranjan
Abstract Micro‐RNAs (miRNAs) are a class of small non‐coding RNAs, recently emerged as a post‐transcriptional regulator having a key role in various cardiac pathologies. Among them, cardiac fibrosis that occurs as a result from an imbalance of extracellular matrix proteins turnover and is a highly debilitating process that eventually lead to organ dysfunction. An emerging theme on is that miRNAs participate in feedback loop with transcription factors that regulate their transcription. NF‐κB, a key transcription factor regulator controls a series of gene program in various cardiac diseases through positive and negative feedback mechanism. But, NF‐κB mediated miRNA regulation in cardiac fibrosis remains obscure. Bioinformatics analysis revealed that miR‐26a has targets collagen I and CTGF and possesses putative NF‐κB binding element in its promoter region. Here, we show that inhibition of NF‐κB in cardiac fibroblast restores miR‐26a expression, attenuating collagen I, and CTGF gene expression in the presence of Ang II, conferring a feedback regulatory mechanism in cardiac fibrosis. The target genes for miR‐26a were confirmed using 3′‐UTR luciferase reporter assays for collagen I and CTGF genes. Using NF‐κB reporter assays, we determine that miR‐26a overexpression inhibits NF‐κB activity. Finally, we show that miR‐26a expression is restored along with the attenuation of collagen I and CTGF genes in cardiac specific IkBa triple mutant transgenic mice (preventing NF‐κB activation) subjected to 4 weeks transverse aortic banding (TAC), compared to wild type (WT) mice. The data indicate a potential role of miR‐26a in cardiac fibrosis and, offer novel therapeutic intervention. J. Cell. Physiol. 228: 1433–1442, 2013. © 2012 Wiley Periodicals, Inc.